PENERAPAN METODE PICTURE AND PICTURE DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II PADA MATA PELAJARAN BAHASA INDONESIA - Razumarda, Sela; Sari, Imelda; Maharani, Siti Dewi (Universitas Negeri Medan, 2023)
The research was carried out with the aim of improving student learning outcomes in Indonesian language subjects. This research includes Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of four stages, namely design, implementation, observation and reflection. The subjects in this research were 22 class IIA students at SDN 238 Palembang. Research data was obtained using teacher and student observation sheets and student test results, then this data was analyzed using a percentage formula. The research results obtained were (1) teacher activity in cycle I using the Picture and Picture method from 80.35% to 92.8% in cycle II, (2) student activity in cycle I using the Picture and Picture 78 method, 57% to 91% in cycle II and (3) the results of learning Indonesian in cycle I using the Picture and Picture method were 63% to 95.45% in cycle II. Based on the results of this research, it can be concluded that by implementing the Picture and Picture model, students' learning outcomes can be more active and teachers' abilities can improve and become better.